CARCASS OF KAMPUNG CHICKEN AT 11 WEEKS WITH DIFFERENT LEVEL OF PROTEIN IN THE RATION - G. A., Nugraha; Nuriyasa, I M.; Puger, A. W. (Jurnal Peternakan Tropika; Vol 6 No 1 (2018): Vol. 6 No. 1 (2018), 2018)
The aims of this research was to findout the effect of the protein level in the ration on the carcass ofkampung chicken at 11 weeks age. This research was carried out for 2 months at the Faculty of Animal Husbandry Research Station, Sesetan, Denpasar. The study used a Completely Randomized Design (CRD) with three treatments and six replicates. Those treatments were rations containing protein 14.5% (R1), rations containing protein 15.5% (R2), and rations containing protein 16.5% (R3). Drinking water and feed were given ad libitum. The variables observed were final weight, carcass weight, carcass percentage, and percentage of carcass component.The results showed that chicken giving rations containing protein 14.5% (R1), rations containing protein 15.5% (R2) and rations containing protein 16.5% (R3) not different (P>0.05) an all of the variables as of final weight, carcass weight, carcass percentage and percentage of carcass component. It can be concluded that chicken giving rations containing protein (14.5%, 15.5% and 16.5%) has no effect on the final weight, carcass weight, carcass percentage, and percentage of  carcass component of kampung chicken at 11 weeks age. Key words: Carcass, Kampung C hicken, L evel of P rotein.